The deepest cut - Tracy, P. J. (Tracy, P. J. Monkeewrench novel, 2025)
"Minneapolis homicide detectives Leo Magozzi and Gino Rolseth arrest a sadistic pair of killers for the murder of several women with the help of Monkeewrench, their eccentric cyber-sleuth friends and partners. One of the killers dies in custody and the other, Wolfgang Mauer, is sent to a maximum security mental hospital in a rural corner of Minnesota. There, Mauer plots his escape--and his vengeance. With the help of his mother, a former militia leader and assassin living an extravagant, reclusive life, he schemes to get out of the mental hospital and hunt down the detectives and the Monkeewrench crew that got him a life sentence. When Mauer successfully escapes, an inexperienced county sheriff is thrown head-first into a massive manhunt for the murderer. When she finds three bodies and discovers that Mauer has kidnapped a young boy, she realizes that Mauer's escape was just the beginning. With many lives on the line, Magozzi, Gino, and Monkeewrench join in the desperate search effort. The longer he's at large, the more people will die, and Mauer is on a mission to find those who sentenced him, so they all have targets on their backs."--Publisher description.